Respuesta :

[tex]3(5x - 4) - (-30-45x)[/tex]
[tex]= 15x - 12 + 30 + 45x[/tex] <- Distributive Property
[tex]=60x + 18[/tex] <- Combine Like Terms

If you're trying to solve for 0:

[tex]0 = 60 x + 18[/tex]
[tex]-18 = 60x[/tex] <- Subtracted 18 from both sides
[tex]x = \frac{-18}{60} = \frac{-9}{30}[/tex] <- Divided both sides by 60 and then simplified.

[tex]x = \frac{-9}{30}[/tex] <- Fraction Form
[tex]x = -0.3[/tex] <- Decimal Form

Give Brainliest for simple answer plz :P

3[5x - 4] - [-30 - 45x] =

Simplifying 3[5x + -4] + -1[-30 + -45x] = 0

Reorder the terms: 3[-4 + 5x] + -1[-30 + -45x] = 0 [-4 * 3 + 5x * 3] + -1[-30 + -45x] = 0 [-12 + 15x] + -1[-30 + -45x] = 0 -12 + 15x + [-30 * -1 + -45x * -1] = 0 -12 + 15x + [30 + 45x] = 0

Reorder the terms: -12 + 30 + 15x + 45x = 0

Combine like terms: -12 + 30 = 18 18 + 15x + 45x = 0

Combine like terms: 15x + 45x = 60x 18 + 60x = 0

Solving 18 + 60x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 60x = 0 + -18

Combine like terms: 18 + -18 = 0 0 + 60x = 0 + -18 60x = 0 + -18

Combine like terms: 0 + -18 = -18 60x = -18

Divide each side by '60'. x = -0.3

Simplifying x = -0.3